2021
DOI: 10.35787/jimdc.v10i1.549
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal trends of Influenza in Islamabad, Pakistan

Abstract: Background: Viral outbreaks have always been a challenging task for clinicians and Influenza virus has been on top of the list. The history of influenza epidemic reveals its devastating effects in the form of multiple deaths and economic burden. Hence this study was planned to recognize the peak activity time span of Influenza infection and its frequency in our set-up at Shifa International Hospital, Islamabad Pakistan. Material and Methods: A cross sectional study was performed in Pathology Laboratory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Another study conducted by Aziz Fat el. has shown a high prevalence of RSV genotype B (20%) in children in Pakistan 21 . Another cross-sectional study conducted by Raza S at el .in Islamabad from April 2016 to March 2019 showed a prevalence of 73.8% for Influenza A virus whereas 26.1% for Influenza B.…”
Section: Resultsmentioning
confidence: 99%
“…Another study conducted by Aziz Fat el. has shown a high prevalence of RSV genotype B (20%) in children in Pakistan 21 . Another cross-sectional study conducted by Raza S at el .in Islamabad from April 2016 to March 2019 showed a prevalence of 73.8% for Influenza A virus whereas 26.1% for Influenza B.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the review of published literature, we summarized the key findings related to influenza epidemiology in Pakistan (Table 2). All the experts agreed that the influenza virus peaks annually in January and February, and that there is a seasonal active window between October and April with sporadic occurrences throughout the summer [19,26,34]. Recently, a cross-sectional study in Islamabad reported that 74% of the patients diagnosed with influenza were type A, among which 62.2% were type A/H1N1.…”
Section: Influenza Epidemiology In Pakistanmentioning
confidence: 98%
“…Recently, a cross-sectional study in Islamabad reported that 74% of the patients diagnosed with influenza were type A, among which 62.2% were type A/H1N1. Most of these cases were detected during January and February [17,19]. This incidence is alarming, especially in an underprivileged population with a lowvaccination rate and weak immunity.…”
Section: Influenza Epidemiology In Pakistanmentioning
confidence: 98%
See 2 more Smart Citations